KARAKTERISTIK TANAH UNTUK TANAMAN Eucalyptus deglupta PADA LAHAN PT. FINANTARA INTIGA SINTANG (Soil Characteristics For Eucalyptus deglupta Plant On Land of PT. Finantara Intiga Sintang) - Tri Widiastuti (Tengkawang : Jurnal Ilmu Kehutanan, 2011)
Characteristics of soil research on land to be planted with Eucalyptus deglupta were examined at HTI PT. Finantara Intiga, Sintang district, the area covered 2241.94 Ha. This study aims to clarity the physical and chemical properties of soil required by this tree species, namely: drainage, texture, effective depth, cation exchange capacity (CEC), pH, and the amounts of N, P and K. Soil sampling was done purposively to consider factors in land cover and slope class. In the study area, land cover was characterized as: secondary forest, plantations of Acacia, coverage of shrubs, varied between 0 to less than 8%. The research area the level of soil drainage class is reduced with an average drainage value of less than 0.5 cm / hour. Soil texture varies from clay to sandy with an effective depth greater than 100 cm, CEC values vary between 9.70 - 18:50 me/100gr. The average soil pH was more about 4.5, N content was 0.04 to 0.15, P content between 1.36 to 0.66 and K content generally smaller than 0.42 me/100gr respectively. Based on the factors mentioned above, the texture, effective depth, CEC and pH of the soil can support the growth of Eucalyptus deglupta, but the soil drainage conditions, the content of N, P and K are not favorable for the species. Keywords : soil characteristics, Eucalyptus deglupta